Tamoxifen Inhibits Cardiac ATP-Sensitive and Acetylcholine-Activated K+ Currents in Part by Interfering With Phosphatidylinositol 4,5-Bisphosphate-Channel Interaction - Daniela Ponce-Balbuena; Eloy G. Moreno-Galindo; Angélica López-Izquierdo; Tania Ferrer; José A. Sánchez-Chapula (Elsevier, 2010)
Tamoxifen inhibits transmembrane currents of the Kir2.x inward rectifier potassium channels by interfering with the interaction of the channels with membrane phosphatidylinositol 4,5-bisphosphate (PIP2). We tested the hypothesis that Kir channels with low affinity for PIP2, like the adenosine triphosphate (ATP)-sensitive K+ channel (KATP) and acetylcholine (ACh)-activated K+ channel (KACh), have at least the same sensitivity to tamoxifen as Kir2.3. We investigated the effects of tamoxifen (0.1 - 10 μM) on Kir6.2/SUR2A (KATP) and Kir3.1/3.4 (KACh) channels expressed in HEK-293 cells and ATP-sensitive K+ current (IKATP) and ACh-activated K+ current (IKACh) in feline atrial myocytes. The onset of tamoxifen inhibition of both IKATP and IKACh was slow (T1/2 approximately 3.5 min) and concentration-dependent but voltage-independent. The time course and degree of inhibition was independent of external or internal drug application. Tamoxifen interacts with the pore forming subunit, Kir6.2, rather than with the SUR subunit. The inhibitory potency of tamoxifen on the Kir6.2/SUR2A channel was decreased by the mutation (C166S) on Kir6.2 and in the continuous presence of PIP2. In atrial myocytes, the mechanism and potency of the effects of tamoxifen on KATP and KACh channels were comparable to those in HEK-293 cells. These data suggest that, similar to its effects on Kir2.x currents, tamoxifen inhibits KATP and KACh currents by interfering with the interaction between the channel and PIP2. Keywords:: adenosine triphosphate-sensitive K+ current (IKATP), inhibition, K+ current activated by muscarinic agonist (IKACh), phosphatidylinositol 4,5-bisphosphate (PIP2), tamoxifen